Bilateral Inguinal Hernia Repair: Laparoscopic Totally Extraperitoneal Versus Open Lichtenstein - Yosypenko, Mykhaylo; Shulyarenko , Oleg V.; Havrylov, Hryhorii O. (Acta medica Lituanica, 2025)
Aim: To compare the outcome of laparoscopic totally extraperitoneal repair versus the open Lichtenstein technique in the treatment of primary bilateral inguinal hernias.Materials and methods: The study design was comprised of a matched and randomized research: a total of 93 patients were enrolled in the study and operated in clinic “Medikom” from 2015 to 2022. The patients were prospectively randomized and divided into two groups: Group 1 (n=45) underwent TEP repair, whereas Group 2 (n=48) received Lichtenstein repair.Result: No statistically significant differences were observed between the groups concerning the mean age, sex, body mass index, patient distribution by hernia type, European Hernia Society hernia type, and ASA score (p>0.05).The operating time in Group 1 was on 10.7% more than in Group 2 (p
Keywords: inguinal hernia; laparoscopic totally extraperitoneal repair; Lichtenstein approach; mesh